Waterlettuce Weevil Neohydronomus affinis Hustache, 1926 (Insecta: Coleoptera: Curculionidae) - Telmah Telmadarrehei; Carey R. Minteer (EDIS, 2023)
Neohydronomus affinis Hustache is known as the waterlettuce weevil (Figure 1). It is a biological control agent of the floating plant, waterlettuce, Pistia stratiotes Linnaeus (Araceae) (O’Brien & Wibmer, 1989; Center et al., 2002). Waterlettuce is found in tropical and subtropical regions of the world. It infests slow-moving streams, waterways, lakes, and rivers, forming dense floating mats that are composed of several rosettes connected by stolons (runner stems). The presence of waterlettuce mats diminishes biological diversity and generates obstructions for boating, waterflow, and aquatic organisms (Cordo & Sosa, 2000; Dray & Center, 2002). Even though waterlettuce was documented by explorer William Bartram in Florida before 1765 (plants-archive.ifas.ufl/plant-directory), it is listed as a class II prohibited aquatic plant in the State of Florida.